Assessing the health of the general population in England: how do the three- and five-level versions of EQ-5D compare?. Issue 1 (December 2015) - Feng, Yan; Devlin, Nancy; Herdman, Mike
Abstract Background The EQ-5D is a brief, generic measure of health status that can be easily incorporated into population health surveys. There are two versions of the EQ-5D for use in adult populations, one with 3 response levels in each of the instrument's 5 dimensions (EQ-5D-3L) and one with 5 levels in each dimension (EQ-5D-5L). We compared the two versions as measures of self-reported health status in representative samples of the English general population. Methods EQ-5D-5L data were available from 996 respondents selected at random from residential postcodes who took part in the EQ-5D-5L value set for England study. EQ-5D-3L data were available from 7294 participants included in the 2012 Health Survey for England. Responses on the 3L and 5L versions of EQ-5D were compared by examining score distributions on the two versions, both in terms of the profile (dimensions) and the EQ-VAS. To determine the extent of variations in score according to respondent characteristics, we analysed health status reporting on the descriptive profile, EQ-5D Index, and EQ-VAS of both versions of EQ-5D by age, sex, and educational background. We usedX 2 to test for differences between respondent categories when analyzing EQ-5D profile data and thet test when analyzing EQ-5D Index and VAS scores. Results The 5L version of EQ-5D led to a considerably reduced ceiling effect and a larger proportion of respondents reporting severe health problems compared to the 3L. The 5L version also led to the use of a wider spread of health states; just 3 health states on the 3L covered 75 % of the sample, compared to 12 states on the 5L. Both versions showed poorer health status in older respondents, females, and those in a lower educational category and the EQ-5D-5L descriptive system, though not the Index or VAS, discriminated better between age groups than the 3L. There were no appreciable differences between the two versions in their ability to discriminate between groups defined by gender or educational level. Conclusions The new, expanded 5L version of EQ-5D may be a more useful instrument for the measurement of health status in population health surveys than the original 3L version.